A influência das disposições culturais no Exame Nacional de Desempenho dos Estudantes do Ensino Superior (ENADE) - Silva, Marcio da (2013)
This work falls within the scope of researches on the school career / academic students of different social groups. This is a study on the performance of Brazilian students in the National Performance Higher Education (ENADE). In this sense, the research aims to investigate the existence of possible relationships between socioeconomic background and academic performance of students of higher education in Enade, seeking to answer the question: socioeconomic status of students can influence their performance on the exam? For this, we used the Sociology of Education Pierre Bourdieu, as this author is responsible for developing studies on trajectories, considering the intrinsically linked to cultural capital inherited from the family and social status, ie, elements which together, gather facts related to positions and social processes essential to understanding the meanings of these positions. The analysis of the data that make up the socioeconomic profile of students as well as the result in the proof of the general education Enade revealed that factors such as the type of school attended in high school and ethnicity exerted influence on the performance achieved by the individuals.